Towards more policy advice: Maximizing the UN's assets to build back better - John Hendra; Max-Otto Baumann (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
In order to effectively assist countries in 'building back better' following the COVID-19 pandemic and returning to a path towards the Sustainable Development Goals (SDGs), the United Nations (UN) and its development entities, organised within the United Nations Development System (UNDS), will need to adjust their approach. They need to respond not just through selected interventions of limited scope, which aim to achieve quick and tangible results, but by providing more and higher quality policy advice to governments for dealing with the deep inequalities laid bare by the pandemic worldwide. The argument for a stronger focus on policy advice directed at high-level decision-makers and delivered through both dialogue and advocacy, is not to deny the importance of service delivery, capacity-building and systems strengthening - other key UN delivery modalities that currently account for the majority of the UN's development activities. Through them, the UN saves lives and helps developing countries reduce their reliance on external support. However, such work often fails to achieve the kind of broader, sustainable impact so urgently needed for ensuring a more equitable and sustainable recovery. The UN has long recognised the importance of policy advice, and UN entities have a unique role to play in helping to implement universal norms and values that have been agreed by UN member states and which should inform any recovery. The recent strengthening of the UN resident coordinator system (2019), which ensures that the on average 18 UN entities per programme country deliver more 'as one', has put the UN in a better position to provide integrated policy advice. Building on these reforms, UN Secretary-General António Guterres recently encouraged a greater role for the UN in the provision of 'integrated policy advice', citing 'persistent challenges in forging integrated policies' (UN, 2020). These 'persistent challenges' to policy advice (or 'upstream work' in UN parlance) also come from structural factors that push UN entities towards implementation or 'downstream' work directed at interventions on the ground. Also, member states have been increasingly reluctant - despite often lofty commitments at the global level - to support policy advice through robust mandates, their own strategic engagement and suitable funding at the level of UN entities. The following actions are recommended to correct disincentives to policy advice: * The UN should define policy advice more clearly as a distinct mode of UN engagement and track good practice from UN country teams to further develop this mode of engagement. * Member states should strengthen their endorsement of UN entities' provision of quality policy advice and request them to undertake concrete steps to expand this mode of engagement. * Resident coordinators need to fully exercise the new roles envisioned by the UNDS reform and lead on policy dialogue in collaboration with the UN entities concerned. * Donors should engage strategically with UN entities through core contributions and non-core partnerships to incentivise, rather than discourage, the provision of increased policy advice.
Keywords: 330